Pembentukan Ruang Bersama dan Ruang Terbuka Hijau di Lingkungan Babatan Pilang RT. 003 RW. 005 - Heristama Anugerah Putra; Josephine Roosandriantini (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The number of settlements that began to appear and develop also increased the population level in an area. Humans are by nature social creatures. Individual someone indirectly lives together with the surrounding environment. This is what triggers each individual must be social with one another. However, along with the times and technological advances today, many individuals often forget this and think more about their respective interests. Time to gather and meet face to face with neighbors, and chat with each other directly or with the surrounding environment is also very minimal. Broadly speaking, the Babatan Pilang community is individual. The background to the problems that have been previously described is the basis for this community service to be able to provide input to the community of Babatan Pilang RT. 003 RW 005. The purpose of this community service is to help the community or housing residents to create a social community. This community service program is carried out by creating and arranging common spaces for socializing.